2016
DOI: 10.1002/2015jd024143
|View full text |Cite
|
Sign up to set email alerts
|

Bias reduction in decadal predictions of West African monsoon rainfall using regional climate models

Abstract: The West African monsoon rainfall is essential for regional food production, and decadal predictions are necessary for policy makers and farmers. However, predictions with global climate models reveal precipitation biases. This study addresses the hypotheses that global prediction biases can be reduced by dynamical downscaling with a multimodel ensemble of three regional climate models (RCMs), a RCM coupled to a global ocean model and a RCM applying more realistic soil initialization and boundary conditions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 90 publications
(162 reference statements)
1
14
0
Order By: Relevance
“…Similar results were obtained by Hansingo and Reason (2009) using a global circulation model, which produces anomalous precipitation along the Angolan and northern Namibian coast by imposing increased Atlantic SST offshore Angola in the forcing data. Furthermore, this work also coincides with the results of Paxian et al (2016), wherein West African rainfall predictions could be improved by reducing the tropical Atlantic SST bias when regional predictions were coupled to a global ocean model. We have shown that the usage of a regional climate model with higher resolved atmospheric processes in combination with corrected SSTs lead to more realistic representation of the atmospheric water cycle similar to results of Paeth et al (2017).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were obtained by Hansingo and Reason (2009) using a global circulation model, which produces anomalous precipitation along the Angolan and northern Namibian coast by imposing increased Atlantic SST offshore Angola in the forcing data. Furthermore, this work also coincides with the results of Paxian et al (2016), wherein West African rainfall predictions could be improved by reducing the tropical Atlantic SST bias when regional predictions were coupled to a global ocean model. We have shown that the usage of a regional climate model with higher resolved atmospheric processes in combination with corrected SSTs lead to more realistic representation of the atmospheric water cycle similar to results of Paeth et al (2017).…”
Section: Discussionsupporting
confidence: 85%
“…These inconsistencies are strongest in the eight outermost gridboxes of the model domain, which are used as lateral forcing in REMO, and weakens within the model domain in which the atmosphere can react freely to the SST. Thirdly, the achieved improvements in simulating the atmospheric water cycle using a corrected Atlantic and Indian SSTs are only valid for this region and experiment setup, and may differ in other experiments configurations as found by Paxian et al (2016). Finally, in this work only one regional climate model was applied for downscaling five years global model forcing data.…”
Section: Discussionmentioning
confidence: 88%
“…Also, both simulations underestimate the latent heat fluxes in the Coast of Guinea, the transitional zone, and over the Sahel. Paxian et al [] and Panitz et al [] relate this uncertainty in CCLM simulations to an impact of land surface conditions and to a misreproduction of the soil water content. Land use and soil characteristics influence the soil moisture that plays a key roll in the partitioning between the surface sensible and latent energy fluxes [ Guillod et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…It comprises 40 z-coordinate vertical levels. These simulations were used in a number of evaluation studies regarding decadal predictions of West African monsoon rainfall (Paxian et al 2016;Paeth et al 2017) and the impact of South Atlantic Anticyclone in the generation of coupled model biases in the Angola-Benguela frontal zone (Cabos et al 2017).…”
Section: Regional Climate Simulationsmentioning
confidence: 99%